2011
DOI: 10.1002/etc.479
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activity of tropical fish food can alter baseline vitellogenin concentrations in male fathead minnow (Pimephales promelas)

Abstract: Abstract-Vitellogenin (VTG) is a precursor of egg-yolk protein and is therefore present at high concentrations in the plasma of female fish. In male fish, VTG concentrations are usually undetectable or low, but can be induced upon exposure to oestrogenic substances either via the water or the diet. This work was carried out to determine the reason for apparently elevated VTG concentrations in unexposed stock male fathead minnow maintained in our laboratory. The results showed clearly that some of the food give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
4
7
1
Order By: Relevance
“…In xenoestrogen-contaminated waters, male M. galloprovincialis , displayed elevated VTG while females did not (Pampanin et al, 2005) yet in D. polymorpha females showed a 40% higher rise in VTG than males (Quinn et al, 2004), and Gagné et al (2001) reported increased VTG in both sexes of E. complanata . In addition, recent reports of estrogenic activity of commercial fish food (Beresford et al, 2011) suggest that feeding regimens may contribute to increases in VTG seen in lab settings; yet the low VTG values in control males in our study indicate a minimal effect from feeding. Thus, the short exposure of 6 hr and/or the 100 μg/L estradiol used here may not have been appropriate for inducing VTG in Elliptio complanata .…”
Section: Discussioncontrasting
confidence: 61%
“…In xenoestrogen-contaminated waters, male M. galloprovincialis , displayed elevated VTG while females did not (Pampanin et al, 2005) yet in D. polymorpha females showed a 40% higher rise in VTG than males (Quinn et al, 2004), and Gagné et al (2001) reported increased VTG in both sexes of E. complanata . In addition, recent reports of estrogenic activity of commercial fish food (Beresford et al, 2011) suggest that feeding regimens may contribute to increases in VTG seen in lab settings; yet the low VTG values in control males in our study indicate a minimal effect from feeding. Thus, the short exposure of 6 hr and/or the 100 μg/L estradiol used here may not have been appropriate for inducing VTG in Elliptio complanata .…”
Section: Discussioncontrasting
confidence: 61%
“…The estrogenicity caused by commercial fish feeds has been reported in previous studies (Miyahara 403 et al, 2003;Matsumoto et al, 2004;Beresford et al, 2011). In the present work, 11 out of 32 diets 404 induced sbER-mediated transcriptional activity.…”
Section: Estrogenic Activity Of Sewage Water 274supporting
confidence: 84%
“…daidzein and genistein, in the bile of these fish (Kausik et al, 1995). In fact, 67 estrogenicity of commercial fish feeds has already been assessed using yeast estrogen-screen assays 68 (Matsumoto et al, 2004) or in vivo experiments (Beresford et al, 2011). 69…”
Section: Quesada Et Al Highlightsmentioning
confidence: 99%
“…Based on measured E2 concentrations in the current study (6 and 12 lg/L), the lack of significant vitellogenin induction (measured as whole-body vitellogenin) compared with the that of the controls (which likely represent baseline vitellogenin concentrations for male fish (Beresford et al 2011)) is consistent with previous studies with adult fathead minnows. One possible explanation is that the actual E2 concentrations that reached the livers in our test fish were not sufficient to induce (significant) vitellogenin expression greater than baseline concentrations.…”
Section: Discussionsupporting
confidence: 55%